Trasmigrazione di piante trasferimenti di concetti: la lettura scientifica ed estetica del paesaggio sud americano in Alexander von Humboldt (Altre Modernità, 2013)
The institution of plant geography as a science in Alexander von Humboldt implies for the first time the emergence of concept of migration concerning plants and animals. But plant geography and the study on vegetation in Humboldt’s books aims to conjugate various natural sciences in order to reach an understanding of the geographical distribution of vegetation. A new approach in South American analysis, connected with an aestethic lecture of Tropical lands of New Word, redefines the idea of “New” thanks to use of analogic concepts based on science and European aestethic lexicon.